Exclusively endoscopic approach to treating gastric perforation caused by an intragastric balloon: case series and literature review - Barrichello Junior, Sérgio Alexandre; Ribeiro, Igor Braga; Fittipaldi-Fernandez, Ricardo José; Hoff, Ana Carolina; de Moura, Diogo Turiani Hourneaux; Minata, Mauricio Kazuyoshi; de Souza, Thiago Ferreira; Galvão Neto, Manoel dos Passos; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2018)
Background and study aims Obesity is a serious disease, resulting in significant morbidity and mortality. Intragastric balloons (IGBs) have been in use since the 1980s. After the insertion of an IGB, complications such as migration of the device and even severe gastric perforation can occur, requiring laparoscopic surgery. Here, we report three cases of gastric perforation after IGB insertion. In all three cases, the perforation was successfully repaired through an exclusively endoscopic approach.